Heisei: The floating bridge of dreams (2019)
The reign of Emperor Akihito, known as the Heisei era, will end on April 30, 2019 when his abdication becomes effective. It has been a period of difficulties for Japan in political, economic and social matters. The most outstanding topics that can help build a basic overview of what happened in these last three decades are presented here.